Analysis of Patient Operation Interest in Sumber Glagah Hospital, Mojokerto Regency - Rofi'in, Mohamad; Suprapto, Sentot Imam (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
A person's interest in services is related to the ability of the service provider to provide services. The purpose of this research is to analyze the influence of perception, service quality, anxiety and type of surgery on patient interest in performing surgery at Sumber Glagah Hospital, Mojokerto Regency. The design of this study is a quantitative analytic study with a cross sectional approach with the focus of the research being aimed at analyzingthe influence of perception, service quality, anxiety and type of surgery on patient interest in performing surgery at Sumber Glagah Hospital, Mojokerto Regency with a population of a number 143 respondents and a sample of 105 respondents who were taken using purposive sampling technique. Data analysis using Linear Regression test.The findings found that Most of the respondents had the perception of a sufficient category as many as 65 respondents (61.9%). Most of the respondents had a sufficient service quality category as many as 66 respondents (62.9%). Most of the respondents had moderate anxiety as many as 61 respondents (58.1%). Most of the respondents had a selective category of operation as many as 92 respondents (87.6%). Most of the respondents have a moderate interest category as many as 69 respondents (65.7%). Based on the results of the Multiple Linear Regression analysis, it shows that with a p-value of 0.000 <0.05, H1 is accepted so it can be concluded that simultaneously there isinfluence perception, quality of service, anxiety and type of surgery on patient interest in performing surgery at Sumber Glagah Hospital, Mojokerto Regency with a magnitude of influence 70.4%. Basically, a person's interest can be influenced by various factors ranging from the patient's point of view, the quality of existing services and even the patient's level of anxiety.